Responsibility of Notary Letter Approval on Under Hands Contract - Tara Jasmine; Arpangi Arpangi; Setyawati Setyawati (Sultan Agung Notary Law Review, 2022)
One of the legal actions by Notary in addition to making an authentic deed is making the ratification of an underhand letter and according an underhand letter (legalization) by a Notary. Underhand letters that need to be ratified include a letter of sale and purchase agreement in which a transaction occurs. In applying and interpreting the meaning, method and form of making an underhand letter ratification, interpretations and contradictions often arise regarding this matter, especially with regard to the Notary's Responsibilities in making underhand letter ratification. The purpose of this study is to understand about the responsibility of a notary in making the ratification of an underhand letter in the theory of legal protection and legal certainty theory. This study used a normative research method with statutory approach and library approach. The results of this study indicate that the form of the agreement in the ratification of the letter under the hands of a Notary with legal protection that the notary has no legal obligation to the agreement made by the party making the agreement. However, legal protection is given through the provision of sanctions to Notaries in accordance with the Notary Position Act if it is proven that the Notary has committed deviant actions or behavior or violates the Notary Position Act and the Notary Code of Ethics. The forms of sanctions given are administrative sanctions, civil sanctions, and other sanctions (criminal sanctions and sanctions for a notary code of ethics).